2021
DOI: 10.3889/oamjms.2021.6040
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors Stroke Prevention Behavior among Hypertension Patient in Indonesia

Abstract: Stroke is the leading cause of death in the World and in Indonesia. Hypertension is a major risk of stroke. Modified stroke risk factors are behavioral factors. The purpose of this study is to identify the factors that influence stroke prevention behavior in hypertensive patients. The research method uses cross sectional. Total participants were 461 hypertensive patients who came to Community Health Center. Sampling technique used  concecutive sampling. The questionnaire used contains demographics, knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Scale 1 means the participants were strongly not sure of being at risk of stroke, scale 2 means not sure, scale 3 means undecided, scale 4 means sure, and scale 5 means very sure. We further categorized the level of awareness based on the prior study [ 14 ]: participants with a Likert scale ≤ 3 were categorized as having a low level of awareness, and those with a Likert scale > 3 were categorized as having a high level of awareness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scale 1 means the participants were strongly not sure of being at risk of stroke, scale 2 means not sure, scale 3 means undecided, scale 4 means sure, and scale 5 means very sure. We further categorized the level of awareness based on the prior study [ 14 ]: participants with a Likert scale ≤ 3 were categorized as having a low level of awareness, and those with a Likert scale > 3 were categorized as having a high level of awareness.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study conducted in Indonesia showed that the majority (65.7%) of hypertensive patients in Indonesia had poor stroke prevention behavior. The most dominant factor contributing to poor stroke prevention behavior was the awareness of stroke [ 14 ]. However, this study mostly focused on factors influencing stroke prevention behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study conducted in Indonesia showed that the majority (65.7%) of hypertension sufferers (a risk factor for stroke) in Indonesia had low stroke prevention. One of the factors that influence stroke prevention behavior is knowledge and awareness about stroke [7]. Increased public awareness of stroke will be beneficial for better stroke prevention strategies, especially for at-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on large cohort studies, high BP is an important risk factor for heart failure, atrial fibrillation, chronic kidney disease, heart valve diseases, aortic syndromes, and dementia, in addition to coronary heart disease and stroke [7]. Factors related to stroke prevention behavior among hypertensive patients include self-efficacy, perception, and awareness of stroke risk [8].…”
Section: Introductionmentioning
confidence: 99%